2009
DOI: 10.3998/ark.5550190.0010.623
|View full text |Cite
|
Sign up to set email alerts
|

Ring closure reactions of bicyclic prolinol and prolin ester enantiomers

Abstract: Starting from the of bicyclic proline ester, ethyl exo-2-azabicyclo[2.2.1]heptane-3-carboxylate (+)-5 several hydantoines and thiohydantoines were prepared by acidic ring closure of the corresponding urea or thiourea derivatives. Enantiomer (-)-5 was reduced to 2-azanorbornylmethanol 12, which was transformed to 5,8-methanooxazolo-and thiazolo[3,4-a]pyridine derivatives. The structures, stereochemistry and relative configurations of the synthesized compounds were proved by NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…The docking study has shown that Ser431 formed a strong covalent bond with the inhibitor [59]. The similar nature of modification has also been reported earlier [60]. It's docking with the PC-POP, as shown in Figure 10, revealed that the sulfur and carbonyl groups of inhibitor formed bonds with the catalytic Ser431 and the two active glycines, Gly430 and Gly353.…”
supporting
confidence: 70%
“…The docking study has shown that Ser431 formed a strong covalent bond with the inhibitor [59]. The similar nature of modification has also been reported earlier [60]. It's docking with the PC-POP, as shown in Figure 10, revealed that the sulfur and carbonyl groups of inhibitor formed bonds with the catalytic Ser431 and the two active glycines, Gly430 and Gly353.…”
supporting
confidence: 70%
“…First, the aza-Diels−Alder (DA) reaction between α-imino ester, in situ derived from ethyl glyoxalate and enantiopure 1-phenylethylamine, and cyclopentadiene was carried out in the presence of TFA and BF 3 • OEt 2 in DCM at −78 °C for 8 h. The DA adduct 352 then was hydrogenated over Pd(OH) 2 /C (5%) in absolute EtOH for 3 days, to give amino ester 353, which was transformed into tricyclic 2-thioxo-imidazolidinone 354, when treated with isothiocyanate in toluene at room temperature overnight, followed by refluxing in the presence of dry HCl in EtOH for 5 h. The yields for the last step are 52−73% (Scheme 100). 171 Imidazo The reaction of 2-amino-1,3,4-thiadiazoles with ethyl bromopyruvate was developed to prepare imidazothiadiazole-6-carboxylates 370. Reactions were conducted in dry EtOH under reflux conditions, for 6 h, and gave 370 in 35−48% yields, which were converted to [1,3,4]thiadiazole[2′,3′:2,3]imidazo [4,5-d]pyridazin-8(7H)-ones 371, when reacted with hydrazine hydrate in EtOH under reflux conditions, followed by treatment with Vilsmeier reagent (Scheme 104).…”
Section: Imidazopyridinesmentioning
confidence: 99%
“…The synthesis of 2-thioxoimidazolidinone 354 was reported starting from ethyl glyoxalate. First, the aza-Diels–Alder (DA) reaction between α-imino ester, in situ derived from ethyl glyoxalate and enantiopure 1-phenylethylamine, and cyclopentadiene was carried out in the presence of TFA and BF 3 ·OEt 2 in DCM at −78 °C for 8 h. The DA adduct 352 then was hydrogenated over Pd­(OH) 2 /C (5%) in absolute EtOH for 3 days, to give amino ester 353 , which was transformed into tricyclic 2-thioxo-imidazolidinone 354 , when treated with isothiocyanate in toluene at room temperature overnight, followed by refluxing in the presence of dry HCl in EtOH for 5 h. The yields for the last step are 52–73% (Scheme ) …”
Section: Synthesis Of N-heterocyclesmentioning
confidence: 99%
“…Likewise, the synthesis of pyrrolo[1,2‐ c ]thiazoles was realized by the cyclization of prolinol derivatives with isothiocyanates in presence of conc. HCl [5f,6a,c] . In contrast, structurally enthralling 3‐thia‐1‐azaspiro compounds are barely explored, albeit their medicinal importance [7] .…”
Section: Introductionmentioning
confidence: 99%